Laser‐Induced Dewetting for Precise Local Generation of Au Nanostructures for Tunable Solar Absorption. Issue 8 (19th May 2016) - Berean, Kyle J.; Sivan, Vijay; Khodasevych, Iryna; Boes, Andreas; Della Gaspera, Enrico; Field, Matthew R.; Kalantar‐Zadeh, Kourosh; Mitchell, Arnan; Rosengarten, Gary
Abstract : A precise and scalable method is introduced for realizing deeply subwavelength nanostructures through laser‐induced dewetting. This fabrication method is used to realize a three layer planar absorber device that allows for highly tunable selective visible–IR light absorption. This large area laser dewetting method uses a 532 nm laser with a μm ranged focal spot on a translation stage allowing for fine pattern control. A range of laser powers from 60 to 130 mW is explored and it is found that three dramatically different structures, all aperiodic and random in nature are developed. An interconnected metallic nanowire network, partially connected nanowire networks, and spherical or elliptically shaped nanoparticles are observed for low, intermediate, and high laser powers, respectively. Optical absorptance spectra demonstrate a noticeable variation in response to the structures formed. A tunable absorption in the visible range is demonstrated and the partially connected nanowires show the greatest enhancement in broadband absorption compared to the other structures. Finite element simulations uncover plasmonic and magnetic resonances as the underlying mechanisms for the absorbing behavior. This high degree of control over the dewetting area makes this technique a suitable candidate for many photonic and solar applications allowing for precise engineering of the absorbing nanostructure design. Abstract : Laser‐induced dewetting provides a method for precise and scalable fabrication of deeply subwavelength nanostructures. This fabrication method is used to realize a three layer planar absorber device that allows for highly tunable selective visible‐IR light absorption. This high degree of control over the dewetting area makes this technique a suitable candidate for many photonic applications allowing for precise engineering.